PELAKSANAAN PEMBELAJARAN PAI BAGI ABK HAMBATAN PENDENGARAN DI SMPLB ISLAM YASINDO TUMPANG MALANG - Afif Tristanti; Syamsu Madyan; Dwi Fitri Wiyono (VICRATINA, 2021)
The application of Islamic religious education learning at the Islamic Junior High School Yasindo Tumpang Malang is an effort so that students with special needs with hearing impairments can develop their faith and create children with noble character. The focus of the research discusses the materials, processes and supporting factors as well as the inhibiting factors of Islamic education learning. To achieve this goal, the researcher used a qualitative method with a case study approach. Researchers found the results of this study include learning materials that are more practical and simple. The learning process includes curriculum, methods, media, communication systems, and learning outcomes. for the supporting factors of this research, namely the high student interest in learning. The inhibiting factor for this research is the condition of students with hearing impairments who have communication difficulties and poor memory.